Exploring the genetic variation of wheat-Triticum timopheevii introgression lines for flowering morphology traits for hybrid wheat use - Othmeni, Manel; Grewal, Surbhi; Walker, Jack; Hubbart-Edwards, Stella; Yang, Cai-yun; Scholefield, Duncan; Ashling, Stephen; King, Ian P.; King, Julie (Frontiers in Plant Science, 2025)
IntroductionThe autogamous nature of wheat presents a significant challenge for hybrid wheat breeding, which relies on cross-pollination. To facilitate hybrid wheat production, it is essential to modify the floral morphology of wheat to promote outbreeding rather than inbreeding. While some genetic diversity for flower morphology exists within wheat, it is limited compared to the vast and largely untapped genetic variation found in its wild relatives for potentially all agronomically important traits, including flowering characteristics. The aim of this study was to identify genomic regions associated with flowering morphology traits in the wild relative Triticum timopheevii.Materials and methodsA set of 24 wheat-T. timopheevii introgression lines were screened for seven flowering-related traits: plant height, spike length, number of spikelets per spike, anther extrusion, filament length, anther length and pollen size.ResultsA significant level of variation was observed among the population for all traits. Phenotyping highlighted the potential of T. timopheevii for enhancing filament length and pollen size for use in hybrid wheat production. Five introgression lines showed significant improvement in filament length or pollen size compared to the parental wheat lines. Through comparative analysis of introgression lines carrying different-sized segments of the same genome and linkage group, specific T. timopheevii genomic regions were identified as carriers of alleles responsible for increased filament length and smaller pollen grains. An inter-crossing strategy between two introgression lines, each carrying different-sized introgressions from Chromosome 5G of T. timopheevii with an overlapping region, was employed to generate a new introgression line with a smaller genomic segment believed to confer the desired trait. Phenotyping of plants with this smaller introgression confirmed the presence of an allele(s) responsible for producing smaller pollen grains.DiscussionThis study demonstrates the potential of T. timopheevii to contribute valuable genetic variation for floral traits critical to hybrid wheat breeding, paving the way for improved outcrossing efficiency and enhanced hybrid seed production.